Public Accountability and Health Care Governance Public Management Reforms Between Austerity and Democracy - Mattei, Paola; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book deals with the critical empirical void created by the speed at which healthcare restructuring has taken place in Europe. Chapters explore the political uncertainty and budgetary pressures which have led governments increasingly to turn to New Public Management (NPM)-style reforms to attempt to balance the financial viability of public health structures, with democratic imperatives to maintain socially just outcomes. The authors of this volume consider how governments have therefore shifted identities from principal care providers to contractual monitors, setting targets increasingly directed toward third-party managers in quasi-markets and the private sector. Drawing upon extensive data from Germany, Norway, the Netherlands, and Israel, the contributions explore the often unexpected policy outputs and outcomes engendered by such reforms.
Keywords: Political science; Public policy; Political Science and International Relations; Public Policy; Electronic books